Optical water types found in Brazilian waters - Silva, Edson Filisbino Freire da; Novo, Evlyn Marcia Leao de Moraes; Lobo, Felipe de Lucia; Barbosa, Claudio Clemente Faria; Noernberg, Mauricio Almeida; Rotta, Luiz Henrique da Silva [UNESP]; Cairo, Carolline Tressmann; Maciel, Daniel Andrade; Flores Junior, Rogerio (Springer, 2020)
Optical water types (OWTs) can represent diverse ranges of Chlorophyll-a (Chl-a), total suspended matter (TSM), and colored dissolved organic matter (CDOM) concentrations, which make them extremely useful for monitoring water quality, for example, detecting eutrophic conditions or tuning remote sensing algorithms. In this study, the objective is to assess OWTs found in Brazilian waters using in situ remote sensing reflectance (R-rs), acquired for water bodies encompassing a wide range of optical characteristics. Eight OWTs are obtained based on R-rs spectral shape and magnitude, which represent different limnological characteristics of Brazilian waters. The OWT 1 is clear waters with low TSM, Chl-a, and CDOM (median ((x) over tilde): TSM of 2.64 g m(-3), Chl-a of 6.04 mg m(-3), and CDOM of 0.6 m(-1)); OWT 2 represents moderate turbid waters (TSM (x) over tilde: 5.14); OWTs 3, 4, and 5 are characterized by waters with high Chl-a concentration ((x) over tilde: 33.1, 39.6, and 180.4 mg m(-3), respectively); OWT 6 is characterized with the highest CDOM concentration ((x) over tilde: 4.07 m(-1)); OWTs 7 and 8 consist of waters with the highest TSM concentrations from terrestrial input ((x) over tilde: 19.55 and 93.25, respectively). Hence, those OWTs could support satellite monitoring by helping to tune algorithms and also providing wide spatial-temporal monitoring.
Keywords: Hyperspectral; Optical properties; Classification